DEBATES ON DIFFERENCES AND INEQUALITIES IN THE CONTEXT OF NATION-BUILDING: PARALLELS BETWEEN INDIA AND BRAZIL - Hofbauer, Andreas [UNESP] (Univ Fed Maranhao, Centro Ciencias Humanas, 2023)
Indian and Brazilian societies present many differences, but they also share similarities that largely relate to their colonial past. They are marked by internal cultural differences and above all by huge social inequalities. In each country, discourses of political and intellectual leaders emerged who sought not only to explain local traditions and the status quo of social relations, but also to suggest political proposals to combat the perceived problems. This article aims to focus on the discourses of four important personalities responsible for the elaboration of approaches that would become paradigmatic references in the discussions in each of the countries: Gandhi vs. Ambedkar; Freyre vs. Fernandes. The analysis seeks to point to oppositions and parallels in the most diverse planes, but especially in the ways in which these thinkers dealt with the topics of differences and inequalities.
Keywords: Difference Inequality; Nation-building; India; Brazil